2001
DOI: 10.1081/drt-100001361
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Moisture Transport in Paper Detected by Magnetic Resonance Imaging

Abstract: Magnetic resonance imaging was used to visualize in-plane moisture transport in laboratory-made handsheets, heavy paperboard, and polyethylene-coated paperboard.Beginning with wet samples sealed on both surfaces, the moisture content was reduced through evaporation from the outside edges. The diffusion of moisture to the outside edges, i.e., in the plane of the sheets, was found to be isotropic with respect to the sample machine and cross directions. Isotropic in-plane moisture diffusion was observed for sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…It has previously been observed that moisture invades into nanocellulose films at two different time-scales (Minelli et al, 2010): Fickian diffusion at short time-scales and a slower moisture uptake at long time-scales which may be due to a relaxation of the cellulose matrix (Minelli et al, 2010). It should be mentioned that a similar, two time-scales sorption behavior is observed for ordinary paper, in which case vapor invades through the pore structure and diffuses into denser regions (Leisen et al, 2001;Ramarao et al, 1995), probably best described by dual transport/sorption models for vapor and condensed phase (Ramarao et al, 2003). However, the typical pore size of NFC films is in the order of the mean free path of water molecules in air, which is approximately 68 nm (Jennings, 1988).…”
Section: Through-thickness Moisture Dynamicsmentioning
confidence: 58%
“…It has previously been observed that moisture invades into nanocellulose films at two different time-scales (Minelli et al, 2010): Fickian diffusion at short time-scales and a slower moisture uptake at long time-scales which may be due to a relaxation of the cellulose matrix (Minelli et al, 2010). It should be mentioned that a similar, two time-scales sorption behavior is observed for ordinary paper, in which case vapor invades through the pore structure and diffuses into denser regions (Leisen et al, 2001;Ramarao et al, 1995), probably best described by dual transport/sorption models for vapor and condensed phase (Ramarao et al, 2003). However, the typical pore size of NFC films is in the order of the mean free path of water molecules in air, which is approximately 68 nm (Jennings, 1988).…”
Section: Through-thickness Moisture Dynamicsmentioning
confidence: 58%
“…There were no significant difference in the behaviour in MD and CD, and thus, a mean value over the densities of the CD and MD samples was calculated for further analysis. The decision is supported by Leisen et al, 18 who report that diffusion of moisture in the plane of the sheet is isotropic.…”
Section: Diffusivitiesmentioning
confidence: 81%
“…18 This result was obtained by exposing round test pieces to a step change in relative humidity, and observing the forced convection drying with magnetic resonance imaging. One of the studied materials was polyethylene coated paperboard.…”
Section: In-plane Diffusion Of Moisturementioning
confidence: 99%
“…Magnetic resonance imaging (MRI) offers one possibility to acquire such data. [75][76][77][78][79] Harding et al [76] achieved a resolution of 15 lm which was sufficient to follow the moisture gradients in a cardboard during drying. Leisen et al [78,79] studied in moisture transport during drying of handsheets and paperboard using a 2 D MRI set-up.…”
Section: Heat and Mass Transfer In The Papermentioning
confidence: 99%